Foreign direct investment (FDI) and agricultural growth in Zimbabwe - Zingwena, Taurai (Midlands State University, 2017)
Low levels of government spending in the agricultural sector over the past years together with poor attraction of external capital are among the major determinants of low agricultural growth in Zimbabwe. The purpose of this research was to examine the impact of (FDI) on agricultural growth in Zimbabwe and to analyze other macroeconomic variables which affect growth in the long run. The exploration of the impact of FDI on agricultural growth was grounded on the growth framework. Secondary data was used for the study and time series data was collected for the period 1980 to 2012 and the study established the determinants of agricultural growth and estimate the impact posed by FDI on growth. The Stock-Watson Dynamic Ordinary Least Squares (DOLS) method was used to analyze the long run elasticities. The study revealed that there exist a positive relationship between FDI and agricultural growth in the long run with an elasticity of 0.07 although it is inelastic. All other macroeconomic variables included in the model have expected signs statistically significant. The study contributed in adding more literature on the relationship between agricultural growth and foreign direct investment. The government should foster policies which create conjusive environments for FDI inflows and should address policies which attract more inflows of FDI